MODEL DEVELOPMENT IN DECISION MAKING ON VILLAGE APPARATUS PERFORMANCE MEASUREMENT AFTER WORKING FROM HOME USING WEIGHTED PRODUCT METHOD - Rita Irviani; Sri Hartati; Muhamad Muslihudin (Jurnal TAM (Technology Acceptance Model), 2022)
These changes in the performance of course affect the effectiveness of public services and the performance of the village apparatus, starting from the service system of the apparatus, the productivity of the apparatus, and the accountability of the apparatus in carrying out government affairs delegated by the Regent. Given the pandemic situation which is gradually easing, the government has again changed the work system for personal public services while still adhering to health protocols. The return of the old model of public administration performance system certainly affects the productivity and accountability of the village apparatus. This research was conducted to measure the Performance of Village Apparatus in Kalirejo Village, Central Lampung using the Weighted Product Method which is a decision-making method using multiplication that connects the value of the criteria, where the value for each criterion must be raised to the power of the weight of the criteria concerned. The Weighted Product Method was chosen because it could complete every existing alternative. The function of the Weighted Product Method determines the weight value for each alternative and the assessment criteria which have been determined. There are seven criteria used in this study. Those criteria are Education, Productivity, Public Service, Quality of Human Resources, Accountability, Facilities, and Income per Per-capita. The results of this study are the development of a model which can be used as a benchmark for assessing village officials in Kalirejo village, Central Lampung as a trial object of research. This decision-making model can also be implemented with a mobile web application for a broader range of measurements with larger data.